Approach to the situational state of the educational rights in the decade of correísta government, Ecuador - Haro-Jácome, Oswaldo (2020)
The study analyzes the situation of the rights of Ecuadorian teachers in the labor and union spheres during the decade of correísta government. This is a necessary investigation in the academy, which includes the assessments of teachers belonging to the public servants sector run by the state. The relevance lies in the description of the dispute between the teachers organized in their guild, the National Union of Educators (UNE), with the governmental power led by the controversial Eco. Rafael Correa, during the 2007-2017 decade. The research is fundamentally qualitative, retrospective, transversal and descriptive. The empirical instrument is the survey applied to a population of 300 teachers in service, investigated during the 2017-2018 school period. In addition, in-depth interviews were applied to professional experts in human rights and citizen participation. As more outstanding results it was found that, mostly, teachers perceive having been subject to violation of their rights, especially labor, union and civil liberties. Systematic effects on teachers, as a professional sector and teachers in particular, were produced by an intentional political action planned by the power of the state. Field data also show that a few teachers appreciate having been benefited by the government.